Fosterage in medieval Ireland - O'Donnell, Thomas author.
1 online resource.
Keywords: Fosterage was a central feature of medieval Irish society, yet the widespread practice of sending children to another family to be cared for until they reached adulthood is a surprisingly neglected topic. Where it has been discussed, fosterage is usually conceptualised and treated as a purely legal institution. This work seeks to outline the emotional impact of growing up within another family. What emerges is a complex picture of deeply felt emotional ties binding the foster family together. These emotions are unique to the social practice of fosterage, and we see the language and feelings originating within the foster family being used to describe other relationships such as those in the monastery or between humans and animals. This book argues that the more we understand how people felt in fosterage, the more we understand medieval Ireland.